2017
DOI: 10.1038/s41598-017-15471-w
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Exacerbates OVA-mediated asthma in mice through C5a-C5aR regulating CD4+T cells Immune Responses

Abstract: Asthma exacerbation could be induced by respiratory syncytial virus (RSV), and the underlying pathogenic mechanism is related to complement activation. Although complement might regulate CD4+T cells immune responses in asthma model, this regulation existed in RSV-induced asthma model remains incompletely characterrized. In this study, we assessed the contribution of C5a-C5aR to CD4+T cell immune responses in RSV-infected asthma mice. Female BALB/C mice were sensitized and challenged with ovalbumin (OVA) while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…These data suggest that C3aR1 regulates the generation of pathogenic neutrophil-recruiting T H 17 responses during hRSV infection [ 260 ]. On the other hand, another study shows that treatment with C5aRA—an antagonist of the C5a receptor—leads to lower pulmonary damage, lower AHR and lower infiltration of neutrophils in the lung and BAL, as well as a reduced viral load in the lung during hRSV infection [ 261 ]. Moreover, AHR and the infiltration of inflammatory cells are also reduced in asthma murine models during hRSV infection [ 261 ].…”
Section: Differential Regulation Of the Innate Immune Response By mentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that C3aR1 regulates the generation of pathogenic neutrophil-recruiting T H 17 responses during hRSV infection [ 260 ]. On the other hand, another study shows that treatment with C5aRA—an antagonist of the C5a receptor—leads to lower pulmonary damage, lower AHR and lower infiltration of neutrophils in the lung and BAL, as well as a reduced viral load in the lung during hRSV infection [ 261 ]. Moreover, AHR and the infiltration of inflammatory cells are also reduced in asthma murine models during hRSV infection [ 261 ].…”
Section: Differential Regulation Of the Innate Immune Response By mentioning
confidence: 99%
“…On the other hand, another study shows that treatment with C5aRA—an antagonist of the C5a receptor—leads to lower pulmonary damage, lower AHR and lower infiltration of neutrophils in the lung and BAL, as well as a reduced viral load in the lung during hRSV infection [ 261 ]. Moreover, AHR and the infiltration of inflammatory cells are also reduced in asthma murine models during hRSV infection [ 261 ]. These data suggest that the activation of C5aR is also pathogenic and enhances AHR and pulmonary infiltration during hRSV infection and is possibly implicated in the control of asthmatic responses [ 261 ].…”
Section: Differential Regulation Of the Innate Immune Response By mentioning
confidence: 99%
See 1 more Smart Citation
“…For 5 mice in each group, the right lung of each animal was dissected for homogenate culture and the left lung for H&E staining. For the other 5 mice in each group, whole lung homogenate was performed as previously described (15). Briefly, whole lung tissue from each animal was prepared by homogenization in PBS-containing protease inhibitors (Complete, Roche Diagnostics).…”
Section: Experimental Designmentioning
confidence: 99%
“…Similar to the symptoms observed in the trial participants, FIRSV has been shown to induce a Th2-biased immune response leading to pulmonary inflammation, airway obstruction and mucus hypersecretion in many animal models, which are now deemed as the hallmarks of vaccine-induced enhanced respiratory disease (ERD) 13 16 . Moreover, non-neutralizing antibodies induced by FIRSV have been implicated in ERD development 17 19 , while another major facet of immunity, subsets of CD4+ T cells, was implicated in mediating various parameters of FIRSV-induced ERD 20 , 21 . However, the contribution of memory CD8 T cells in providing protection against RSV re-infection remains to be fully understood in spite of their known importance in viral clearance 20 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%